Memory, History, Cognition: Using Systems-Theoretical Social Theory to Illuminate Patrick Modiano’s enquêtes policières - Gunderson, Kristen (Cahiers d'histoire, 2022)
Winner of the 2014 Nobel Prize in literature, Patrick Modiano is perhaps the most widely known contemporary French author uniting individual memory and collective historical narrative. His novels, detective-like investigations, focus on the German Occupation of France during World War II. This article argues that Modiano’s detective investigations may best be read as a mise-en-scene of processes of cognition, using the work of social scientist Niklas Luhmann, whose theory of how individual and collective systems “make sense” using memory, perception, and other cognitive phenomena addresses certain particularities present in Modiano’s work. The idea of witness plays a crucial role in both Modiano’s oeuvre and Luhmann’s model of cognition.